Relasi Tuntutan Reformasi Politik dan Kemenangan Move Forward Party pada Pemilihan Umum Tahun 2023 di Thailand - Fadhila, Muhammad Zahran; Hidayat, Cecep (Jurnal Review Politik, 2024)
For almost ten years, Thailand was governed by a military junta that staged a coup. It disappointed the Thai people as there were problems with civil liberties and economic growth. These problems led to demands for political reform in 2020-2021. On the other hand, the Move Forward Party, as an opposition party with a reformist program, won a significant victory in the 2023 general election. Therefore, this research examines the relationship between the demands for political reform and the triumph of the Move Forward Party in 2023. The data comes from a literature study that helps trace the stages of demands for political reform and the relationship between activists and opposition political parties in Thailand. The analysis using the concept of collective identity evolution shows that the movement demanding political reform disseminated through social media effectively unites the aspirations of the Thai people. Meanwhile, analysis using a socio-electoral coalition shows a reciprocal relationship between political reform activists and the Move Forward Party during the 2023 General Election in Thailand